The Ethics of Embryo Adoption and the Catholic Tradition Moral Arguments, Economic Reality and Social Analysis - Brakman, Sarah-Vaughan; Fozard Weaver, Darlene (Catholic Studies in Bioethics ;, 2007)
At last, a comprehensive collection of essays that examines and advances ethical evaluations of the controversial and increasingly popular practice of embryo adoption. In the United States alone, 400,000 frozen embryos created for in vitro fertilization exist but are no longer desired for that purpose. What are we morally obliged or permitted to do about these "spare" embryos? More of their genetic parents are considering donating these embryos to others to gestate and raise. This practice is politically volatile (figuring in debates about embryonic stem cells) and medically and morally complex. At the present time within the Roman Catholic Church there is no official teaching on embryo adoption. Catholic ethical analyses grapple with the way embryo adoption comports with respect for embryonic human life yet challenges Catholic moral critiques of assisted reproductive technologies. This volume brings together leading philosophers and theologians to engage Catholic debates about embryo adoption in an interactive format. The editors, a philosopher bioethicist and a moral theologian, provide a helpful overview of the practice and the arguments surrounding embryo adoption. They engage neglected Catholic ethical resources and issues to advance the current debate and chart new directions in Catholic moral thinking about this intriguing practice. The volume also includes a description of embryo adoption from a physician practitioner along with reflections from a couple who successfully adopted an embryo.